Performing the Prophetic. (3rd July 2019) - Wagner, Matthew
ABSTRACT: Hamlet's first encounter with the Ghost serves principally, in narrative terms at least, to deliver the news, both to the play's protagonist and its audience, that Claudius is a treasonous, fratricidal villain. But Hamlet's response – "O my prophetic soul! / My uncle!" – encompasses the possibility that Hamlet suspected his uncle's guilt. This essay begins by asking why Hamlet's suspicion might be framed as prophetic, and it suggests that some answers lie in the state of unease that accompanies performed moments of prophecy, and, moreover, that this unease is, at heart, temporal in nature. Theatre – and Shakespearean theatre especially – is adept at unsettling our sense of time, and both the articulation of and the resistance to prophecy in Hamlet generate fluctuations in our experience of temporality in performance. The essay traces this argument across key moments in the play that are particularly marked by prophecy, suggesting that across these moments, the play weaves a pattern of unsettling, then calming, then again disturbing our sense of the theatrical world, by way of manipulating our sense of time through the performance of the prophetic.